1997
DOI: 10.1002/(sici)1096-8628(19970418)74:2<167::aid-ajmg10>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Longer brainstem auditory evoked response latencies of individuals with fragile X syndrome related to sedation

Abstract: Brainstem auditory evoked response latencies were studies in 75 males (13 with fragile X syndrome, 18 with mental retardation due to other causes, and 44 with no disability). Latency values were obtained for each ear for the positive deflections of waves I (P1), III (P3), and V (P5). Some individuals with mental retardation required sedation. Contrary to previous report, latencies obtained for individuals with fragile X did not differ from those obtained for persons without mental retardation. Persons receivin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…It is thus possible that the detected ABR alterations may have resulted indirectly from impaired middle ear function. Indeed, more recent studies from FXS individuals without middle ear infection did not find any differences in the absolute peak latencies and IPLs of ABRs . However, one should be careful in attempting to interpret this result as implying that ABRs and FMRP expression are independent.…”
Section: Fmrp Regulates the Development Of Synaptic Transmission In Tmentioning
confidence: 89%
See 1 more Smart Citation
“…It is thus possible that the detected ABR alterations may have resulted indirectly from impaired middle ear function. Indeed, more recent studies from FXS individuals without middle ear infection did not find any differences in the absolute peak latencies and IPLs of ABRs . However, one should be careful in attempting to interpret this result as implying that ABRs and FMRP expression are independent.…”
Section: Fmrp Regulates the Development Of Synaptic Transmission In Tmentioning
confidence: 89%
“…Because more than half of FXS children have otitis media, individuals without this peripheral pathology present only a specific population of FXS who are probably less sensitive to FMRP loss in both the periphery and the central nervous system. Other work compared children with FXS, with or without receiving sedation, during ABR testing and argued that differences seen in ABR testing across studies may be caused by the administration of sedatives . However, this study may have over‐sampled from high‐functional patients who may have been more tolerant of the ABR test.…”
Section: Fmrp Regulates the Development Of Synaptic Transmission In Tmentioning
confidence: 99%
“…Abnormalities consisting of prolongation of waves and increased interpeak latency intervals have been reported in a number of mental retardation syndromes [7] patients with head trauma [8], and hydrocephalus [9]. However, there have been some documented effects of sedation on the interpeak latency intervals of the ABR in children with mental retardation [10], in other neurologic disorders such as central alveolar hypoventilation [11,12] as well as in patients with respiratory insufficiency following encephalitis [13]. Due to the documented effects of sedation on estimates of interpeak latency intervals in some clinical populations, it has been suggested that abnormal interpeak latency intervals reported in patient populations such as fragile × syndrome may be related to the use of sedation as opposed to inherent features of the disorder [10].…”
Section: Introductionmentioning
confidence: 99%
“…However, there have been some documented effects of sedation on the interpeak latency intervals of the ABR in children with mental retardation [10], in other neurologic disorders such as central alveolar hypoventilation [11,12] as well as in patients with respiratory insufficiency following encephalitis [13]. Due to the documented effects of sedation on estimates of interpeak latency intervals in some clinical populations, it has been suggested that abnormal interpeak latency intervals reported in patient populations such as fragile × syndrome may be related to the use of sedation as opposed to inherent features of the disorder [10]. Miezejeski et al [10] demonstrated that irrespective of diagnosis, patients with mental retardation who were sedated for testing had longer III-V interpeak latency intervals than non-sedated patients with mental retardation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation